The management of human potential (Docentes 2.0 Journal, 2018)
To talk about people management is to talk about influx, mind, intelligence, vitality, action and proaction. People management is one of the areas that has undergone more changes and transformations in recent years. These have not only unbalanced their tangible and concrete aspects but, above all, have modified the conceptual and intangible aspects.
Keywords: management; human potential